Thrust Areas of Machine Learning and Its Current Scenario - M, Vasumathy (International Journal of Computer Sciences and Engineering, 2019)
Machine Learning counter in this world beyond the buzzwords to transfigure our living cosmoses. It is made conceivable by the convergence of lively data. Traditionally, Machine learning (ML) is multi-disciplinary inclusive of statistics and computer science in around of computational systems from the collective data prediction than instructions. ML functions to the base fact of predictions of data on the reality of applications. Thence the thrust areas of Machine Learning with its bias are explicated here with certain reality and comprehensive examples like Trusting Scientific Discoveries Made Possible, Facing Volatile Price Trends for Tomato Growers, Gaining Critical Mass for Data Analytics Pros and Finding Hidden Technologies in IIOT. The techno ML is majorly bounded with rule and behavior-based systems, Bayesian and statistical algorithm, Neural Network and Deep Neural Network are also exposed here with their specification and its learning style is deliberated.